خطأ التمسك المطلق بمبدأ فصل السلطات لدفع اختصاص القضاء الإداري - الذاري محمد عبدالرحمن (Journal of Amran University, 2023)
An extrapolation of many administrative court cases indicates that the defendant administrative authorities seek to evade discussing the subject matter of the case، on the pretext that the administrative judge’s discussion of issues related to administration is considered interference in its work, in contradiction to the principle of separation of powers, and the same objection can be raised before the Constitutional Court when The dispute over a legal text. This indicates that there is confusion in understanding the principle, and a complete lack of awareness of the reality of the function of the judiciary, which is characterized by a specificity that distinguishes it from the functions of the executive and legislative authorities. In addition to impartiality and objectivity، which are the two qualities necessary for those who undertake the settlement of disputes. In addition, invoking the principle before the judiciary in order to disrupt its role contradicts the requirement of the principle of legality that rulers submit to the law before individuals, which is embodied here by complying with the judiciary and respecting its decisions.